Determination of aluminum from water samples and dialysis fluids after separation/preconcentration on Duolite XAD-761 polymeric resin. Issue 15 (27th March 2016) - Ciftci, Harun; Er, Cigdem; Ozkan, Mustafa
Abstract: In the present study, a new solid-phase extraction method was developed for the separation and preconcentration of trace aluminum in various water samples. The 4-(2-pyridylazo) resorcinol was used as a chelating agent for adsorption of aluminum ions from aqueous solutions on Duolite XAD-761 polymeric resin. Various experimental parameters such as pH of sample solution, volume, and concentration of eluent, flow rate of sample solution, sample and solution volume, amount of ligand and adsorbent, matrix effects for preconcentration, and capacity of adsorbent were investigated. The developed procedure was successfully applied to dialysis fluids and some water samples.